EFFECT OF MICRORNA-138 ON EPITHELIAL-MESENCHYMAL TRANSITION AND INVASION OF BREAST CANCER CELLS BY TARGETING SEMAPHORIN 4C - HuiJuan Liu (Taylor & Francis Group, 2021)
In view of the role of miR-138 in cancer cells, we predicted the target of miR-138 and its targeting to SEMA4C by bioinformatics software and luciferase experiment. The expression levels of miR-138 in human normal breast epithelial cells and two kinds of BC cells were compared, and the transfection cells were selected. MiR-138 mimetic negative control (miR-NC), miR-138 mimic and miR-138 inhibitor were designed for cell transfection. The results showed that the expression level of miR-138 in MCF-7 cells was the lowest. The up regulation of miR-138 would lead to the high expression of E-cad and the low expression of N-cad, vim and SEMA4C, and the vitality and invasion of BC cells would decrease. The down regulation of miR-138 would lead to the low expression of E-cad and the high expression of N-cad, vim and SEMA4C, and the vitality and invasion of BC cells would increase. miR-138 targeted regulation of SEMA4C can promote the expression of N-cad, inhibit the expression of E-cad, vim and SEMA4C, reverse the EMT of BC cells, and inhibit the activity and invasion of BC cells. MiR-138 has clinical potential as a tumor marker of BC.